2000
DOI: 10.1093/heapol/15.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and applying a minimum basic needs approach in southern Philippines

Abstract: This study, a collaboration between Canadian and Filipino researchers, focuses on how the national government's Minimum Basic Needs (MBN) Approach has been implemented at the local level in some selected sites in Region XI on the Philippine island of Mindanao. This case study of MBN implementation focuses on the experiences of three municipalities and three barangays (villages) within them. The research explores, through interviews and group discussions, what the mayors, technical working groups and volunteer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Details of the quality assessment for the way each study was reported in the papers included in this review are given in Supplementary file 4; 10 papers were found to report a high quality of evidence, (Sandiford et al 1994; Heinonen et al 2000; Mubyazi et al 2004; Chaulagai et al 2005; Mutemwa 2006; Soeung et al 2006; Maluka et al 2010, 2011a; Nnaji et al 2010; La Vincente et al 2013) and four to report an acceptable quality (Murthy 1998; de Savigny et al 2008; Maluka et al 2011b; Mutale et al 2013). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the quality assessment for the way each study was reported in the papers included in this review are given in Supplementary file 4; 10 papers were found to report a high quality of evidence, (Sandiford et al 1994; Heinonen et al 2000; Mubyazi et al 2004; Chaulagai et al 2005; Mutemwa 2006; Soeung et al 2006; Maluka et al 2010, 2011a; Nnaji et al 2010; La Vincente et al 2013) and four to report an acceptable quality (Murthy 1998; de Savigny et al 2008; Maluka et al 2011b; Mutale et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Mubyazi et al (2004) TanzaniaCase series in 4 districtsDistrict Commissioners, Administrative Secretaries, Medical Officers, Health Secretaries, Treasurers, Hospital Medical Superintendents; Council Executive Directors, Health Officers and Planning Officers; Dispensary and Health centre staff; Village leaders and development committees; Ward Development Committees; Heads of households+++ 12. Heinonen et al (2000) PhilippinesCase studyAdministrators, Health Managers, General population+++ 13. Murthy (1998) IndiaCase series in 2 districtsNGO programme officers, District Health Officer, District Family Welfare Officer, Primary health centre staff++ 14.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The central and local governments provide basic emergency care in hospitals, child and maternal care services through clinics, and public health services including safe water and other environmental health programs. The Philippine government has worked hard to improve the quality and accessibility of primary health care through various programs, but success has been limited (Heinonen et al 2000).…”
Section: Health Care Servicesmentioning
confidence: 99%